Two turtles with soft tissue preservation from the platy limestones of Germany provide evidence for marine flipper adaptations in Late Jurassic thalassochelydians. - Walter G Joyce (Public Library of Science (PLoS), 2021)
Late Jurassic deposits across Europe have yielded a rich fauna of extinct turtles. Although many of these turtles are recovered from marine deposits, it is unclear which of these taxa are habitually marine and which may be riverine species washed into nearby basins, as adaptations to open marine conditions are yet to be found. Two new fossils from the Late Jurassic of Germany provide unusually strong evidence for open marine adaptations. The first specimen is a partial shell and articulated hind limb from the Late Jurassic (early Tithonian) platy limestones of Schernfeld near Eichstätt, which preserves the integument of the hind limb as an imprint. The skin is fully covered by flat, polygonal scales, which stiffen the pes into a paddle. Although taxonomic attribution is not possible, similarities are apparent with Thalassemys. The second specimen is a large, articulated skeleton with hypertrophied limbs referable to Thalassemys bruntrutana from the Late Jurassic (early Late Kimmeridgian) platy limestone of Wattendorf, near Bamberg. Even though the skin is preserved as a phosphatic film, the scales are not preserved. This specimen can nevertheless be inferred to have had paddles stiffened by scales based on the pose in which they are preserved, the presence of epibionts between the digits, and by full morphological correspondence to the specimen from Schernfeld. An analysis of scalation in extant turtles demonstrated that elongate flippers stiffed by scales are a marine adaptation, in contrast to the elongate but flexible flippers of riverine turtles. Phylogenetic analysis suggests that Thalassemys bruntrutana is referable to the mostly Late Jurassic turtle clade Thalassochelydia. The marine adapted flippers of this taxon therefore evolved convergently with those of later clades of marine turtles. Although thalassochelydian fossils are restricted to Europe, with one notable exception from Argentina, their open marine adaptations combined with the interconnectivity of Jurassic oceans predict that the clade must have been even more wide-spread during that time.